2014
DOI: 10.1155/2014/898453
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Computational Model of a Methane Producing Archaeum

Abstract: Progress towards a complete model of the methanogenic archaeum Methanosarcina acetivorans is reported. We characterized size distribution of the cells using differential interference contrast microscopy, finding them to be ellipsoidal with mean length and width of 2.9 μm and 2.3 μm, respectively, when grown on methanol and 30% smaller when grown on acetate. We used the single molecule pull down (SiMPull) technique to measure average copy number of the Mcr complex and ribosomes. A kinetic model for the methanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 89 publications
2
9
0
Order By: Relevance
“…SiMPull is a sensitive way of measuring the concentrations of proteins in cells because it can detect changes in picomolar concentrations in the cell lysate. The copy number per cell can be estimated based on number of cells used, and the sample volume . SiMPull is also a very reproducible and robust way of estimating concentrations because we found that similar numbers of proteins are pulled‐down at a specific concentration each time the experiment is repeated (within about 20% error) .…”
Section: Concepts Behind Simpullmentioning
confidence: 88%
See 1 more Smart Citation
“…SiMPull is a sensitive way of measuring the concentrations of proteins in cells because it can detect changes in picomolar concentrations in the cell lysate. The copy number per cell can be estimated based on number of cells used, and the sample volume . SiMPull is also a very reproducible and robust way of estimating concentrations because we found that similar numbers of proteins are pulled‐down at a specific concentration each time the experiment is repeated (within about 20% error) .…”
Section: Concepts Behind Simpullmentioning
confidence: 88%
“…In this review, we will discuss the detailed methodology of the assay. We will highlight how SiMPull can be extended to diverse biological macromolecules, not just proteins , and serve as a valuable tool for characterizing various biochemical properties and processes . We will conclude by extending the applications of SiMPull to the realm of biosensors, and draw comparisons with other major biosensing techniques presently available.…”
Section: Introductionmentioning
confidence: 99%
“…RNA was isolated as previously reported [85]. Briefly, M. acetivorans C2A wild type was adapted to grown, TMA or acetate for 33 generations.…”
Section: Methodsmentioning
confidence: 99%
“…Selective pull-down is achieved through capture of a bait protein using a high-affinity antibody either specific for the bait protein itself or to a purification tag appended to the protein (TAP, Flag, etc). The immobilized bait is then typically used to capture one or more, fluorescently-labeled prey protein (as well as any interacting partners that might form a complex) in order to study stoichiometry of the bait-prey complex (Bharill, Fu, Palty & Isacoff, 2014; Jain et al, 2011; Panter, Jain, Leonhardt, Ha & Cresswell, 2012; Peterson, Labhsetwar, Ellermeier, Kohler, Jain, Ha, et al, 2014; Shen, Chakraborty, Jain, Giri, Ha, Prasanth, et al, 2012) or conformational dynamics of a protein or protein complex (Zhou, Kunzelmann, Webb & Ha, 2011; Zhou, Zhang, Bochman, Zakian & Ha, 2014). …”
Section: Experimental Methodsmentioning
confidence: 99%